Serological survey of HIV and syphilis in pregnant women in Madagascar. Issue 1 (24th October 2012) - Frickmann, Hagen; Schwarz, Norbert G.; Girmann, Mirko; Hagen, Ralf M.; Poppert, Sven; Crusius, Sabine; Podbielski, Andreas; Heriniaina, Jean N.; Razafindrabe, Tsiriniaina; Rakotondrainiarivelo, Jean P.; May, Jürgen; Rakotozandrindrainy, Raphaël
Abstract Objectives Peripartal transmission of human immunodeficiency virus (HIV) and Treponema pallidum, the causative agent of syphilis, leads to severe consequences for newborns. Preventive measures require awareness of the maternal infection. Although HIV and syphilis testing in Madagascar could be theoretically carried out within the framework of the national pregnancy follow‐up scheme, the required test kits are rarely available at peripheral health centres. In this study, we screened blood samples of pregnant Madagascan women for HIV and syphilis seroprevalence to estimate the demand for systemic screening in pregnancy. Methods Retrospective anonymous serological analysis for HIV and syphilis was performed in plasma samples from 1232 pregnant women that were taken between May and July 2010 in Ambositra, Ifanadiana, Manakara, Mananjary, Moramanga and Tsiroanomandidy (Madagascar) during pregnancy follow‐up. Screening was based on Treponema pallidum haemagglutination tests for syphilis and rapid tests for HIV, with confirmation of positive screening results on line assays. Results Out of 1232 pregnant women, none were seropositive for HIV and 37 (3%) were seropositive for Treponema pallidum. Conclusions Our findings are in line with previous studies that describe considerable syphilis prevalence in the rural Madagascan population. The results suggest a need for screening to prevent peripartal Treponema pallidum transmission, while HIV is still rare. If they are known, Treponema pallidum infections can be easily, safely and inexpensively treated even in pregnancy to reduce the risk of transmission.